2000
DOI: 10.1097/00006842-200007000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Body Image Dissatisfaction on Subsequent Psychological and Physical Adjustment After Disfiguring Injury

Abstract: Body image dissatisfaction affects quality of life after severe burn injury. Distress moderates this impact on aspects of physical but not psychosocial health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 22 publications
1
66
0
12
Order By: Relevance
“…Previous studies showed that clinically significant body image dissatisfaction was associated with lower scores in both the mental and the physical subscales of SF-36 [32] and predicted psycho-social functioning at 12 months post-discharge, mediating the effect of gender, TBSA, and pre-burn quality of life [33].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies showed that clinically significant body image dissatisfaction was associated with lower scores in both the mental and the physical subscales of SF-36 [32] and predicted psycho-social functioning at 12 months post-discharge, mediating the effect of gender, TBSA, and pre-burn quality of life [33].…”
Section: Discussionmentioning
confidence: 94%
“…Factors related with the treatment experience, including painful procedures experienced while in hospital, involvement in self-care and unreal expectations in the rehabilitation phase, are shown in Figure 3 and were mentioned in four studies. E-VI Meanings attributed to procedure experience during hospitalization (9,29) ; self-care encouragement (31) E-VII Unreal expectations during rehabilitation (45) E-VI Post-traumatic stress (6,10,46) anguish (30,33,47) ; psychological vulnerability and feelings of threat (30) ; anxiety (12,31) ; dissatisfaction with body image (48)(49) ; depressão (25,34) E-VII Post-traumatic stress (45) Factors related with burn trauma and severity…”
Section: Psychological Factorsmentioning
confidence: 99%
“…E-V Burn location (40) E-VI Burned body surface (3)(4)6,30,34,38,42,48,(50)(51)(52)(53) ; burns on hands (27,34,38) , on feet (27) , in the face (27,34,48) ; burn location (8,42) ; burn severity (3)(4)6,11,20,22,24,42) ; scars (39) ; facial disfigurement(46); limb amputation (11,46) ; time after injury (30,54) , intolerance to cold (55) , to heat (49,55) ; to sunlight (12,55) , itching (55) , numbness (55) , disfigurement (21,55) , sleeping problems (55) , care dependence (55) ; pain (24,(27)(28)33) ; weakness …”
Section: Psychological Factorsmentioning
confidence: 99%
“…Fauerbach et al found that pre-burn affective disorder, but not anxiety disorders, increased the risk of post-burn PTSD. 16 In another study, cosmetic disfigurement was related to the manifestation of PTSD symptoms of avoidance and emotional numbing in females injured by burn. Furthermore, personality traits have been related to PTSD after burn.…”
mentioning
confidence: 96%
“…A study by Fauerbach et al indicated that neuroticism was higher, and extraversion was lower in patients who developed PTSD compared with those who did not develop PTSD. 16 Scandinavian personality theorist, Henrik Sjöbring postulated three personality variants which he labelled Validity, Stability and Solidity. Partly based on the theories of Sjöbring, as well as on other theories on biologically based dimensions of personality, Daisy Schalling developed the Karolinska Scales of Personality (KSP).…”
mentioning
confidence: 99%